2005
DOI: 10.21273/hortsci.40.3.645
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Daily Light Integral on Bedding Plant Growth and Flowering

Abstract: Daily light integral (DLI) describes the rate at which photosynthetically active radiation is delivered over a 24-hour period and is a useful measurement for describing the greenhouse light environment. A study was conducted to quantify the growth and flowering responses of bedding plants to DLI. Eight bedding plant species [ageratum (Ageratum houstonianum L.), begonia (Begonia ×semperflorens-cultorum L.), impatiens ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 5 publications
(6 reference statements)
14
97
1
Order By: Relevance
“…Obviously, excessive light inhibited growth of runner plants, which was supported by evidences that net photosynthetic rate, F v /F m and chlorophyll content of runner plant leaves under highest DLI were at lowest level. Similar results on bedding plants were reported that the total plant dry mass increased at a decreasing rate as DLI increased from 5 mol/(m 2 ·d) to 43 mol/(m 2 ·d), and the maximum peak point varied with specific species [24] . However, everbearing strawberry 'HS138' had 1.4-1.5 times greater dry matter accumulation in the plants at a high DLI (29.2 mol/(m 2 ·d)) than at a low DLI (19.4 mol/(m 2 ·d)), and no adverse effects on plants were found under high DLI and continuous lighting [25,26] .…”
Section: Effects Of Light Intensity and Photoperiod On Propagation Ofsupporting
confidence: 86%
“…Obviously, excessive light inhibited growth of runner plants, which was supported by evidences that net photosynthetic rate, F v /F m and chlorophyll content of runner plant leaves under highest DLI were at lowest level. Similar results on bedding plants were reported that the total plant dry mass increased at a decreasing rate as DLI increased from 5 mol/(m 2 ·d) to 43 mol/(m 2 ·d), and the maximum peak point varied with specific species [24] . However, everbearing strawberry 'HS138' had 1.4-1.5 times greater dry matter accumulation in the plants at a high DLI (29.2 mol/(m 2 ·d)) than at a low DLI (19.4 mol/(m 2 ·d)), and no adverse effects on plants were found under high DLI and continuous lighting [25,26] .…”
Section: Effects Of Light Intensity and Photoperiod On Propagation Ofsupporting
confidence: 86%
“…In several cases, response to production environment differed between the three crops investigated in our study. This was expected as plant growth and TTF response to light and temperature are well known to vary according to plant species and cultivar (Blanchard and Runkle, 2011b;Faust et al, 2005;Mattson and Erwin, 2005).…”
Section: Resultsmentioning
confidence: 84%
“…Additionally, we postulate that suppression of stem elongation in the HT was influenced by the higher DLI. Increasing DLI has been shown to reduce stem elongation, during both constant and diurnal temperatures regimens (Faust et al, 2005;Kaczperski et al, 1991). For example, plant height of 'Snow Cloud' petunia grown at a constant air temperature of 15°C was reduced by 32% as DLI increased from 6.5 to 13 mol · m -2 · d -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher stem caliper, RDM, and SDM were observed under HPS and LED SL compared with seedlings grown under ambient radiation, although differences between the SL sources were not observed. Generally, an increased DLI results in increased dry mass per unit of fresh weight, which ultimately leads to thicker tissues (Faust et al, 2005). Multiple studies have shown that increased DLI leads to increases in the accumulation of RDM and SDM of young plants (Hern andez and Kubota, 2014;Lopez and Runkle, 2008;Oh et al, 2010;Poel and Runkle, 2017b).…”
Section: Discussionmentioning
confidence: 99%